Challenges, Interference, and Coping Strategies in English Communication of Balinese Cruise Ship Crew Members in a Multilingual Context - Wedhanti, Nyoman Karina; Yuliasri, Issy; Pratama, Hendi; Sakhiyya, Zulfa (International Journal of Language Education, 2025)
In the linguistically varied environment of foreign cruise ships, strategic English use as a lingua franca determines how well multinational crews communicate. This study examines challenges, interference, and coping strategies in English communication in a multilingual context of Balinese cruise ship crew members who have spent more than ten years working for an international cruise company. The data of the study were collected using in-depth semi-structured interviews with nine deliberately selected participants. The collected data were analyzed using thematic analysis to examine their communication challenges, inferences, and copings strategies they develop in response to English communication-related issues. Results reveal the challenges that the Balinese cruise ship crew members faced were the variety of the English pronunciation and accent of the speakers from Japan, India, Russia, and China. In terms of interferences, The Balinese crew members’ English exhibited structural errors influenced by interference from Balinese and Indonesian. These errors, shaped by differences in their native languages, included issues with article usage, verb conjugation, and sentence construction. The This study also confirmed that Balinese cruise ship crew members demonstrated a range of adaptive strategies and coping methods to manage these challenges. In situations where verbal understanding was lacking, they primarily relied on context, nonverbal cues, and interpreting the situation to grasp meaning. To enhance clarity, particularly during guest interactions, they also employed techniques such as rephrasing, repeating information, and simplifying their language. These results highlight the resiliency and adaptability of Balinese cruise ship crew members and provide an understanding of English as a working language in international cruise ship professional environments.